2021
DOI: 10.4018/jgim.20210701.oa2
|View full text |Cite
|
Sign up to set email alerts
|

How Does Social Media Use Influence the Relationship Between Emotional Labor and Burnout?

Abstract: This study used data from an online questionnaire survey of public employees in Ghana and examined the relationship between emotional labor (surface acting and deep acting) and burnout (emotional exhaustion), as well as the moderating-mediating effects of social media use on that relationship. Surface acting has been found to be a stronger predictor of burnout than deep acting. Social media use reinforces the influence of surface acting on burnout but does not moderate the relationship between deep acting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 144 publications
(161 reference statements)
1
15
0
Order By: Relevance
“…In addition, high permeability (e.g., instant messages, or social media) indeed increased the work exhaustion of employees in the context of telecommuting and ICT usage after work (Addas & Pinsonneault, 2018;Leung & Zhang, 2017); and the permeability characteristics was not included in the study of Ayyagari et al (2011). Organizational employees have to work exceptionally hard, spend longer hours at work, and are connected to the organization 24/7 via IT (Addas & Pinsonneault, 2018;Galluch et al, 2015;Nam & Kabutey, 2021); thus, the supervisor's work-related instant messages (IM) after working hours of the employees will increase their work exhaustion and dissatisfaction of their company (D'Arcy et al, 2014).…”
Section: Data Analysis Relationships and Discussionmentioning
confidence: 99%
“…In addition, high permeability (e.g., instant messages, or social media) indeed increased the work exhaustion of employees in the context of telecommuting and ICT usage after work (Addas & Pinsonneault, 2018;Leung & Zhang, 2017); and the permeability characteristics was not included in the study of Ayyagari et al (2011). Organizational employees have to work exceptionally hard, spend longer hours at work, and are connected to the organization 24/7 via IT (Addas & Pinsonneault, 2018;Galluch et al, 2015;Nam & Kabutey, 2021); thus, the supervisor's work-related instant messages (IM) after working hours of the employees will increase their work exhaustion and dissatisfaction of their company (D'Arcy et al, 2014).…”
Section: Data Analysis Relationships and Discussionmentioning
confidence: 99%
“…Tandon et al [ 87 ] found that this behavior induced voyeurism and fear of missing out and compulsive use of social media among employees. Nam and Kabutey [ 88 ] noted that this behavior enhances the impact of emotional labor on burnout, which leads to emotional exhaustion. Whelan et al [ 89 ] found that this behavior amplified the effects of information overload on social media fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Social support can both enhance one's available resources and can replace or provide other resources that have been lacking (Hobfoll, 1989). For example, the empirical study of Nam and Kabutey (2021) finds that social media use at work may help employees conserve them of personal resources (Nam & Kabutey, 2021). Therefore, as an external resource, it can timely compensate streamers for the internal resources consumed in emotional labor during the live streaming.…”
Section: Social Support and Emotional Labormentioning
confidence: 99%
“…Recent research shows that social support is effective to reduce emotional exhaustion (Nam & Kabutey, 2021), because it helps to reinforce the positive aspects of the self, in essence self-concept when stressful times have led one to lose sight of them (Swann & Predmore, 1985). As a kind of self-concept, professional identity reflects one's perceptions regarding a professional role (Dobrow & Higgins, 2005).…”
Section: The Mediating Effect Of Professional Identitymentioning
confidence: 99%